Longer Screws Can Reduce the Stress on the Upper Instrumented Vertebra With Long Spinal Fusion Surgery: A Finite Element Analysis Study. Issue 4 (May 2023) - Oe, Shin; Narita, Kengo; Hasegawa, Kazuhiro; Natarajan, Raghu N.; Yamato, Yu; Hasegawa, Tomohiko; Yoshida, Go; Banno, Tomohiro; Arima, Hideyuki; Mihara, Yuki; Ushirozako, Hiroki; Ide, Koichiro; et al.
Study Design: A finite element analysis study. Objective: Of proximal junctional failure, upper instrumented vertebra (UIV) fracture can causes severe spinal cord injury. Previously, we reported that higher occupancy rate of pedicle screw (ORPS) at UIV prevented UIV fracture in adult spinal deformity surgery; we had not yet tested this finding using a biomechanical study. The purpose of present study was to measure the differences in loads on the UIV according to the length of PS and ORPS. Methods: We designed an FE model of a lumbar spine (L1-S1) using FE software. The PS was set from L2 to S1 and connected the rod. The FE model simulated flexion (8 Nm) to investigate the loads at UIV (L2) according to the length of the PS. There were 5 screw lengths examined: 40 (ORPS 36.4%), 45 (48.5%), 50 (66.7%), 55 (81.8%), and 60 mm (93.9%). Results: Stress with bending motion was likely to occur at the upper front edge of the vertebral body, the pedicles, and the screw insertion point. The maximum equivalent stress according to screw lengths of 40, 45, 50, 55, and 60 mm were 45.6, 37.2, 21.6, 13.3, and 14.8 MPa, respectively. The longer screw, the less stress was applied to UIV. No remarkable change was observed between the screw lengths of 55 and 60 mm. Conclusions: Increasing ORPS to 81.8% or more reduced the load on the UIV. To prevent UIV fracture, the PS length in the UIV should be more than ORPS 81.8%.